(untitled) (Journal of Parents and Teachers, 2025)
The article emphasizes the importance of transmitting and contributing to teacher training through the media. Within journalistic genres, there are several items or subdivisions: informative, opinion, and advertising. Additionally, the text should be understandable, engaging, clear, and concise. And, of course, it should include titles, subtitles, and headings.